AL-BERUNIY INTERNATIONAL SCHOOL IN TASHKENT (Academicia Globe: Inderscience Research, 2023)
The Al-Beruniy International School in Tashkent offers a modern and inclusive educational experience for both local and expatriate students. With a focus on providing a holistic education, the school offers a wide range of co-curricular activities such as sports, music, art, and debates. Additionally, the school prioritizes language learning, offering classes in various world languages. Its diverse student community helps foster a sense of global citizenship, and state-of-the-art facilities create a supportive learning environment. Overall, Al-Beruniy International School is a leading institution in Tashkent that prepares students for success in a rapidly becoming globalized world.